2009
DOI: 10.1108/17473610910964688
|View full text |Cite
|
Sign up to set email alerts
|

The influence of money attitudes on young Chinese consumers' compulsive buying

Abstract: Purpose -The purpose of this paper is to investigate how young Chinese consumers' money attitudes influence their compulsive buying behavior.Design/methodology/approach -In total, 303 undergraduate students from Tianjin and Ningbo (two major cities in coastal China) answered a self-administered questionnaire.Findings -Money attitudes were found to significantly affect young Chinese consumers' compulsive buying behaviour. Specifically, the Retention-Time dimension significantly affected both male and female con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 19 publications
2
37
0
3
Order By: Relevance
“…New consumers are searching for differentiation, brand and origin reputation, luxury goods and status symbols, and they participate in conspicuous consumption. These trends derive from the Chinese social evolution highlighted by several scholars (Bi et al, 2012;Li et al, 2009;Lin & Wang, 2010;Taylor, 2014;Wang et al, 2013;Zhao & Belk, 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…New consumers are searching for differentiation, brand and origin reputation, luxury goods and status symbols, and they participate in conspicuous consumption. These trends derive from the Chinese social evolution highlighted by several scholars (Bi et al, 2012;Li et al, 2009;Lin & Wang, 2010;Taylor, 2014;Wang et al, 2013;Zhao & Belk, 2007).…”
Section: Discussionmentioning
confidence: 98%
“…These characteristics underlie the modern Chinese consumer, who pursues luxury, adopts a western lifestyle, prefers foreign products and is influenced by the country of a product's origin (Bi et al, 2012;Li, Jiang, An, Shen, & Jin, 2009;Zhao & Belk, 2007). Wine is a beverage in line with the expectations of this consumer.…”
Section: Chinese Consumer and Wine Preferencesmentioning
confidence: 99%
“…Thus the Little Emperor generation is a very attractive market segment and with regard to their spending patterns, Wang (2009) claims that, 'while older consumers are not likely to build up credit card debts because they have known poverty, young consumers in the cities have started to spend more using credit cards, as instant gratification, rather than patience is likely to be their norm'. Further research on China's Little Emperors, reported by Li et al (2009), examined how young Chinese consumers' attitudes towards money affected their compulsive buying behaviour and how gender moderates such a relationship. Their research results show that the consideration of money as a means to buy high quality products and brands increases compulsive buying among Chinese young consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to those possible new developments Thompson and Worthington (2010) referred to Wang (2009), who suggested that younger consumers in the cities started to show increased spending behavior as well as increased use of credit cards to seek for instant gratification. Li et al (2009) showed that the tension between the temptation to use money for demonstrating a high status and the obligation to save money plays an important role for compulsive buying in China. Furthermore they report that a high power-prestige orientation has an influence on compulsive buying, which is moderated by gender: young men show a higher influence of a high power-prestige orientation on compulsive buying than young women, whereas Li et al (2009) also report a higher compulsive buying rate for young women.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the mentioned studies show that cultural factors do play an essential role for the emergence of compulsive buying. In contrast to studies about impulsive buying in China or other Asian markets (Fengjie, 2011;8 A. Unger and G. Raab Gutierrez, 2004;Yeung & Yee, 2009;Zhou & Wong, 2003), only a few studies about compulsive buying in China or Asia are yet published (Li, Jiang, An, Shen, & Jin, 2009). The same is the case for cross-cultural studies about compulsive buying.…”
Section: Compulsive Buying: Theoretical Considerations and Empirical mentioning
confidence: 99%